The Effect Of Reproductive Health Education Through Video Media on Adolescent Knowledge About The KRR TRIAD On SMA Negeri 2 Kuta - Kadek Ayu Trisnayanti; Ni Komang Yuni Rahyani; I Gusti Agung Ayu Novya Dewi (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2024)
Globally health problems in adolescents triggered by risky adolescent behavior such as unhealthy dating, smoking, consuming alcohol and using drugs are a major concern worldwide. The research aims to prove the effect of reproductive health education through video media on adolescents' knowledge about TRIAD ARH (Sexuality, HIV/AIDS, and Drugs). This type of research is Quasi Experimental Design with a pretest-posttest design with a control group design. The sample for this research was class XI SMA Negeri 2 Kuta, consisting of 42 respondents in the control group and 42 respondents in the experimental group using the probability sampling technique with the proportional random sampling method. Data analysis used the Wilcoxon and Mann Whitney tests. The results showed that there was an increase in the average knowledge before and after being given health education in the control group and the experimental group (p value 0.000). The knowledge of the control group obtained a mean rank of 32.55 and the experimental group obtained a mean rank of 52.45 (p value 0.000). These results indicate that there is an influence of reproductive health education through video media on youth's knowledge of TRIAD KRR (Sexuality, HIV/AIDS, and Drugs). Future research is expected to be able to carry out different interventions regarding TRIAD KRR in adolescents.